Carbon-13 chemical shift tensors of disaccharides: measurement, computation and assignment. - Shao, L; Yates, JR; Titman, J (2007)
A recently developed chemical shift anisotropy amplification solid-state nuclear magnetic resonance (NMR) experiment is applied to the measurement of the chemical shift tensors in three disaccharides: sucrose, maltose, and trehalose. The measured tensor principal values are compared with those calculated from first principles using density functional theory within the planewave-pseudopotential approach. In addition, a method of assigning poorly dispersed NMR spectra, based on comparing experimental and calculated shift anisotropies as well as isotropic shifts, is demonstrated.